PENGEMBANGAN PERANGKAT LUNAK DENGAN MENGGUNAKAN PHP - Haryana, KM. Syarif (STMIK Mardira Indonesia, Bandung, 2008)
PHP is a web-based programming language in which the system is implemented on the server side . PHP can be inserted between the HTML language scripts and other server side language arena , with it then PHP will be executed directly on the server . While the browser will execute the web page through which the server will then receive the display